Applying ultrasonic resonance vibrometry for the evaluation of impact damage in natural/synthetic fibre reinforced composites. (July 2018) - Derusova, D.A.; Vavilov, V.P.; Sfarra, S.; Sarasini, F.; Druzhinin, N.V.
Abstract: Contemporary thermoset composites using natural fibres offer a wide range of strength performance. Recently, the combination of flax and carbon fibres has received an increasing attention, mainly dictated by the possibility of merging in a single material high damping properties of flax fibres and the well-known high mechanical properties of carbon fibres. Evaluation of low energy impact damage defects has received a little coverage even if these composites are well known to be susceptible to impact damage. In this study, the use of ultrasonic resonance vibrometry is proposed as an effective nondestructive tool to detect the extent of impact damage in natural/synthetic fibre reinforced composites with different stacking sequences. The results for impacts at 10 and 40 J highlighted the role played by the different stacking sequences with damaged areas being twice smaller in composites with flax skins and carbon core compared to carbon-flax-carbon sandwiches. Highlights: The use of natural/synthetic composite hybridization allows improving damage tolerance in compared to carbon laminates. Scanning laser vibrometry is a promising technique for inspecting impact damage in natural fibre reinforced composites. Low velocity impacts result in energy absorption through internal damages and global elastic-plastic deformation. Single discontinuities represent independent oscillators characterized by particular resonance frequencies. The defect size and location can be easily detected by the help of total vibration pattern.